A comparative analysis on materials and resources in green assessment tools for various countries - Naamandadin, Nurul Akmam; Yahya, Norhaizura; Sapian, Abdul Razak (Trans Tech Publications, Switzerland, 2016)
The concept of sustainable building incorporates and integrates a variety of strategies during the design, construction and operation of building projects. The use of green building materials and products represents one important strategy in the design of a building. Green building materials offer specific benefits to the building owner and building occupants such as reducing maintenance/replacement costs over the life of the building, energy conservation, improving occupant health and productivity, and greater design flexibility. Thus, the aim of this paper is to identify the similarities and the differences for the selected green assessment tools which can be obtained stage by stage of the RIBA Outline Plan of Work 2013. The study had been carried out through a comparative analysis. The finding is predicted to help the construction industry practitioners to be able to understand the assessment criteria involved at every stages in the construction process concerning on material and resources. Especially for those who are concerned on green building and to sustain our natural environment.